Outcomes of patients with severe mitral regurgitation treated with transcatheter mitral valve implantation or medical therapy. (4th February 2022) - Ludwig, S; Sedighian, S; Weimann, J; Koell, B; Waldschmidt, L; Schaefer, A; Seiffert, M; Westermann, D; Reichenspurner, H; Blankenberg, S; Schofer, N; Lubos, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with severe mitral regurgitation (MR) unsuitable for standard therapy (i.e., open-heart surgery and transcatheter edge-to-edge repair [TEER]), often remain on medical therapy (MT) alone. Transcatheter mitral valve implantation (TMVI) may represent an alternative treatment option for these patients. Purpose: We aimed to investigate differences in anatomical baseline characteristics and echocardiographic outcomes between MR patients unsuitable for standard therapy, that were either treated with TMVI or remained on MT. Methods: Between 05/2016-02/2021, 121 high-risk patients with severe MR were evaluated for TMVI. Clinical, echocardiographic and functional outcomes between the subgroups of patients treated with TMVI and MT were compared. The primary combined endpoint was all-cause death or heart failure (HF) hospitalization at 1 year. Subgroup analyses were performed to define specific patient subsets favouring either TMVI or MT. Results: At baseline, there were no differences between the TMVI group (n = 38) and the MT group (n = 44) regarding age (all TMVI vs. MT: 77.0 years [IQR 72.9, 80.1] vs. 79.0 [IQR 76.0, 81.7], p = 0.13), gender (42.1% female vs. 56.8% female, p = 0.27) and estimated surgical risk (EuroSCORE II 4.4% [IQR 2.8, 13.6] vs. 6.4 [IQR 3.4, 10.1], p = 0.72). Patients undergoing TMVI were more frequently treated for secondary MR (68.4%), while primary MR was the most prevalent MR etiology in patients remaining on medical therapy (50.0%). Left ventricular (LV) end-diastolic diameters (LVEDD) were larger and LV ejection fraction (LVEF) was lower in the TMVI group (LVEDD 58.0mm [IQR 51.4, 65.0], LVEF 37.0% [IQR 31.4, 51.2]) compared to the MT group (LVEDD 52.0mm [IQR 46.2, 58.8], LVEF 54.5% [IQR 40.8, 60.0]) (p = 0.02 for LVEDD, p < 0.001 for LVEF). MR was effectively reduced to ≤ mild MR in all patients undergoing TMVI. In the MT group, MR remained severe in 90% of patients after 1 year. The primary composite endpoint occurred numerically more often in the MT group (72.2%) compared to the TMVI group (51.6%, p = 0.061). Regarding the primary endpoint, the subgroups of patients with LVEF 30-49% (HR 0.28 [95%-CI 0.11-0.67], p = 0.004), effective regurgitant orifice area (EROA) <0.4 cm2 (HR 0.30 [95%-CI 0.13-0.71], p = 0.006), tricuspid annular plane systolic excursion (TAPSE) ≥17mm (HR 0.27 [95%-CI 0.11-0.67], p = 0.005) and New York Heart Association functional class III (HR 0.38 [95%-CI 0.18-0.81], p = 0.012) were more likely to benefit from TMVI compared to MT. Conclusions: In patients with severe MR unsuitable for standard therapy, TMVI represents a reasonable therapeutic alternative yielding effective elimination of MR. While most patients eligible for TMVI suffer from secondary MR, the majority of patients remaining on MT has primary MR. The primary endpoint occurred numerically, yet not statistically, more often in patients on MT. Baseline echocardiography was able to identify subgroups of patients with beneficial outcome after TMVI.